Efektivitas Implementasi Kebijakan Pelayanan Publik terhadap Tingkat Kepuasan Masyarakat: Studi di Kecamatan Koto Tangah Kota Padang - Ramadhani, Shafira; Jumiati, Jumiati; Dasti, Dafina Permata; Farhan, M.; Aureliyan, Marcya Titania; Saputra, Boni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
Quality public service is a very important aspect to create good governance in the region. The success of implementing public policy does not only depend on the content of the regulation, but also on how the policy can be implemented in adaptive, responsive, and community satisfaction-focused service practices. This article aims to examine the effectiveness of implementing public service policies and the level of community satisfaction with services in Koto Tangah District, Padang City. The approach used in this article is a literature review that examines various reference sources. The results of the discussion show that public services in Koto Tangah District, Padang City still face a number of obstacles related to efficiency, speed of process, and openness of information to the public. This finding underlines the urgency of continuous evaluation of community needs and consistent improvement in the quality of public service management.